Source Apportionment of PM2.5 in Daejeon Metropolitan Region during January and May to June 2021 in Korea Using a Hybrid Receptor Model - Sang-Woo Han; Hung-Soo Joo; Hui-Jun Song; Su-Bin Lee; Jin-Seok Han (Atmosphere, 2022)
We tried to estimate anthropogenic emission sources, including the contributions of neighboring regions, that affect the fine particle concentration (PM2.5) in Daejeon using positive matrix factorization (PMF), concentration weight trajectory (CWT), and modified concentration weight trajectory (MCWT) models in a manner that might overcome the limitations of widely applied hybrid receptor models. Fractions of ion, carbonaceous compound and elements in PM2.5 were 58%, 17%, and 3.6% during January and 49%, 17%, and 14.9% during May to June, respectively. The fraction of ions was higher during winter season, while the fraction of elements was higher during the other season. From the PMF model, seven factors were determined, including dust/soil, sea salt, secondary nitrate/chloride, secondary sulfate, industry, coal combustion, and vehicle sources. Secondary sulfate showed the highest contribution followed by secondary nitrate/chloride and vehicle sources. The MCWT model significantly improved the performance of regional contributions of the CWT model, which had shown a high contribution from the Yellow Sea where there are no emission sources. According to the MCWT results, regional contributions to PM2.5 in the Daejeon metropolitan region were highest from eastern and southern China, followed by Russia, northeastern China, and Manchuria. We conclude that the MCWT model is more useful than the CWT model to estimate the regional influence of the PM2.5 concentrations. This approach can be used as a reference tool for studies to further improve on the limitations of hybrid receptor models.